Pencegahan Kejahatan Digital Dimasa Sekarang Melalui Pendidikan Kewarganegaraan - Amelia Widiana; Wahyu Ramadhan; Reza Mauldy Raharja (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research is aimed to find out about digital crime prevention in today's trough civic education. The method used in this research is a qualitative description of viewing data in moderation. The digital age presents a variety of ease and opportunities for society. But underneath it all, there is a dark side to be aware of, is a digital crime. Digital crime is against the laws of digital technology, such as online fraud, data theft, and hate speech. Citizenship education helps students understand the risks and dangers associated with digital crime, and it gives them the skills to protect themselves and actively participate in the digital world.Through citizen education, individuals gain a deeper understanding of their rights, obligations, honesty and responsibilities as responsible citizens when using digital technology and online ethics. With effective education, we can reduce the risk of digital crime and build a society to deal wisely with it.